Analisis Yuridis Rehabilitasi Narkoba Dalam Sistem Hukum Pidana Indonesia - Firman Nurhidayah Riyadi; Wahyu Prawesthi; Subekti .; Noenik Soekorini (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
This study aims to analyze the implementation of drug rehabilitation policies within the Indonesian criminal justice system, particularly for drug addicts and victims. Rehabilitation is understood as a humanist approach based on restorative justice, focusing on recovery, not punishment. Although it is regulated by Law Number 35 of 2009 and several supporting regulations, the implementation of this policy has not been optimal. This study uses a normative juridical method with statutory regulations, conceptualization, and case studies. The results indicate that weak implementation of integrated assessments, limited rehabilitation institutions, social stigma, and disparities in understanding among law enforcement officials are the main obstacles. Data shows that the majority of drug abusers are only sentenced to prison, leading to prison overcrowding and low rehabilitation effectiveness. To achieve the goals of rehabilitation, policy reform is needed through strengthening regulations, standardizing therapy methods, improving human resource competency, and cross-sector integration. This study recommends that rehabilitation be viewed not merely as an alternative punishment, but as an integral, preventive, and corrective criminal policy strategy to create a recovery process that is rehabilitative, socially functional, and prevents relapse.